Pengaruh Terapi Senam dan Pendidikan Kesehatan Hipertensi terhadap Penurunan Tekanan Darah pada Warga dengan Hipertensi - Anita Agustina; Ridha Purwantie; Ridho Setiawan; Siti Nor Wafiyah (JURNAL KEPERAWATAN MERSI, 2026)
Background: Hypertension is a chronic disease and a major risk factor for cardiovascular disorders, remaining a significant public health issue. Non-pharmacological approaches such as hypertension exercise and health education are effective strategies for blood pressure control. Objective: This study aimed to determine the effect of hypertension exercise therapy and health education on reducing blood pressure among hypertensive individuals. Methods: This study used a quasi-experimental design with a one-group pretest–posttest approach. A total of 33 respondents were selected using total sampling. The intervention included hypertension exercise for 20–30 minutes and health education for 10–15 minutes. Blood pressure was measured before and after the intervention. Data were analyzed using a paired t-test. Results: The results showed that 87% of respondents experienced a decrease in blood pressure. There was a significant reduction in systolic (p=0.000) and diastolic blood pressure (p=0.026). Conclusion: It is concluded that hypertension exercise combined with health education is effective in reducing blood pressure.